Aberrant expression of long non-coding RNAs (lncRNAs) is involved in brain glioma development - Ding, Yi (Arch Med Sci, 2019)
INTRODUCTION: Aberrant expression of long non-coding RNAs (lncRNAs) has been implicated in various diseases, including cancer. However, little is known about lncRNAs in human brain gliomas. MATERIAL AND METHODS: We examined lncRNA profiles from three glioma specimens using lncRNA expression profiling microarrays. Quantitative real-time RT-PCR was used to analyze the differential expression of raw intensities of lncRNA expression in glioma and peritumoral tissues. RESULTS: We found 4858 lncRNAs to be differentially expressed between tumor tissue and peritumoral tissue. Of these, 2845 lncRNAs were up-regulated (fold change > 3.0) and 2013 were down-regulated (fold change < 1/3). A total of 4084 messenger RNAs were also differentially expressed, including 2280 up-regulated transcripts (fold change > 3.0) and 1804 that were down-regulated (fold change < 1/3). Consistent with the microarray data, qPCR confirmed differential expression of these 6 lncRNAs (ak125809, ak098473, uc002ehu.1, bc043564, NR_027322, and uc003qmb.2) between tumor and peritumoral tissue. We next established co-expression networks of differentially expressed lncRNAs and mRNAs. Many mRNAs, such as LOC729991, NUDCD1, SHC3, PDGFA, and MDM2, and lncRNAs, such as ENST00000425922, ENST00000455568, uc002ukz.1, ENST00000502715, and NR_027873, have been shown to play important roles in glioma development. Consistent with this, pathway analysis revealed that “GLIOMA” (KEGG Pathway ID: hsa05214) was significantly enriched in tumor tissue. CONCLUSIONS: Our data suggest that altered expression of lncRNAs may be a critical determinant of tumorigenesis in glioma patients.